2021
DOI: 10.1002/chem.202003872
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Response and Self‐Assembly of a Tweezer‐Type Synthetic Receptor Triggered by Complexation with Heme and Its Catabolites

Abstract: There is increasing interest in the development and applications of synthetic receptors that recognize target biomolecules in aqueous media. We have developed a new tweezer‐type synthetic receptor that gives a significant fluorescence response upon complexation with heme in aqueous solution at pH 7.4. The synthetic receptor consists of a tweezer‐type heme recognition site and sulfo‐Cy5 as a hydrophilic fluorophore. The receptor–heme complex exhibits a supramolecular amphiphilic character that facilitates the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…S1†). 25 In that study, we found that a synthetic receptor bearing sulfo-Cy5 (Fig. S1b†) exhibits a change in the fluorescence intensity between pH 6 and 8 probably due to the self-assembly through the protonation and deprotonation of the 4-AQ moiety, 25 b although precise details were not determined.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…S1†). 25 In that study, we found that a synthetic receptor bearing sulfo-Cy5 (Fig. S1b†) exhibits a change in the fluorescence intensity between pH 6 and 8 probably due to the self-assembly through the protonation and deprotonation of the 4-AQ moiety, 25 b although precise details were not determined.…”
Section: Resultsmentioning
confidence: 91%
“…The pH-dependent change in the UV-Vis absorption spectra (Fig. S3b†) suggests that 1 mostly exists in its diprotonated form at pH 5.5, 25,32 and that electrostatic repulsion was alleviated by the electrostatic screening effect imparted by 0.10 M NaCl. 12,13 The absorbance of 1 at 330 nm continuously decreased when increasing the pH from 5.5 to 7.8.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations